Design and construction of left ventricular heart assisting model - Fakhoury, Mohammad; Farrah, Mahmoud; Jwelies, Nabeel (جامعة بوليتكنك فلسطين - اجهزة طبية, 2014)
LVAD stands for Left Ventricular Assist Device. It is a mechanical device that circulates blood throughout the body when the heart is too weak to pump blood by its own. LVAD is designed to perform the pumping function of the patient’s left ventricle. The device is placed just below the diaphragm in the abdomen. It is attached to the left ventricle via one way valve, and the aorta, the main artery that carries oxygenated blood from the left ventricle to the hole body. The system includes a small controller and two batteries is attached by an external driveline. A brushless dc pump push blood from left ventricle to aorta this pump is controlled by (ArduinoController ). The system is synchronized with the patient's ECG , ECG provides information about the patient’s physiological conditions, the external controller is connected to the internal pump through drive line. The System Controller has two power lead cables one for each side that have to be connected to batteries, the speed of the pump, battery level and many physiological parameter are monitored of displayed on the LCD screen. VII ملخص المشروع (LVAD) جهاز مساعد البطين االيسر , هو عبارة عن جهاز الكتروميكانيكي صمّم ليساعد احد البطينين أو كالهما لضخ الدم إلى ارجاء الجسم , فهو اليحل محل القلب وإنما يعمل كمساعد له, بعض هذه االجهزة تستخدم على المدى القصير كعملية عبور إلى ان يتم الحصول على قلب مانح )متب ّرع( أو إلى ان يتعافى المريض من نوبة قلبية اقتضت مساعدة الجهاز في عملية تنظيم ضخ الدم,في حين ان هناك بعض من تلك االجهزة تستخدم على المدى الطويل ,كحال المرضى الذين يعانون من فشل القلب المزمن واليستطيعون ان يخضعوا لعملية زرع قلب نظرا ألحد العوامل التي تحول دون ذلك كأمراض الكلى وأمراض االنسداد الرئوي المزمن وغيرها . يتكون النظام من مضخة ميكانيكية تعمل على تدفق الدم من األدين االيسر الى الشريان االبهر وذلك ضمن متحكم دقيق يعمل على معالجة عدد نبضات القلب للمريض بحيث يقوم من خالل معرفة عدد النبضات بالتحكم بكمية التدفق الذي يحتاجها الجسم , يحصل المريض على المعلومات الكاملة عن حالته و اداء النظام من خالل شاشة عرض تقوم بعرض سرعة نبضات القلب و سرعة المضخة وايضا , وفي حال حدث خلل او فقد ألشارة قلب المريض فأن ً حالة المريض ومعلمات اخرى النظام يقوم بالتحول الى نظام األمان وهنالك تنبيه صوتي وكتابي بأن هنالك خلل ما ويعمل النظام بتدفق دم متوسط ليبقي المريض على قيد الحياة .
no of pages 69, 27300, اجهزة طبية 1/2014, in the store
Keywords: left ventricular heart assisting model